Pengendalian Kapabilitas Proses Produksi Bintang Todjoe di PT. Bintang Todjoe - Ramadhanti, Lifia Citra; Rakay Edhiargo Toyosito; Sugiarto, Emaria (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2024)
PT. Bintang Toedjoe as a company engaged in the manufacturing industry in carrying out its business activities has implemented a production quality control system. The company has even won the ISO 9001 certificate as an acknowledgement that the company has implemented good quality management and in accordance with the applicable quality standard guidelines. Various quality control programs are carried out by the company so that it can produce good products and in accordance with the quality standards set. However, in fact the quality is determined based on the production results theoretically has not reached the specified requirements. As it is known that one of the products of PT. Bintang Todjoe is a traditional medicine, namely Bintang Toedjoe cataches a cold, where this product is a new product released by PT. Bintang Toedjoe. Therefore, a quality control system must be established to ensure that each product produced meets the spesifications set by following standard procedures. One of the quality control programs using statistical quality control, among others, to conduct process capability analysis, namely by testing the normality of the quality parameters of the resulting product and studying the production process capabilities of PT. Bintang Todjoe.